2018
DOI: 10.3892/ol.2018.9679
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin expression in epidermal stem cells in skin adnexal tumors

Abstract: The expression levels of seven types of cytokeratin (CK) in different kinds of skin adnexal tumors were evaluated. One hundred and thirty-two patients with different kinds of skin adnexal tumors admitted and treated in the Department of Dermatology of Dongying People's Hospital from May 2013 to May 2015 were selected and underwent tissue section staining. Another 20 cases of normal skin were enrolled as the control group. The expression levels of the seven types of CK in different kinds of skin appendages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Through measuring the level of cytokeratins 15 and 19 among the patients in comparison with control, we found that cytokeratins are expressed in [21] who studied these CKs expression in adnexal neoplasm in comparison with normal subjects. When CKs were measured in the patients after they received NB-UVB for 4 th months, they are found higher than control and this agrees with Goldstein et al [22] who reported the effect of NB-UVB on proliferation and differentiation of Melscs.…”
Section: Discussionsupporting
confidence: 86%
“…Through measuring the level of cytokeratins 15 and 19 among the patients in comparison with control, we found that cytokeratins are expressed in [21] who studied these CKs expression in adnexal neoplasm in comparison with normal subjects. When CKs were measured in the patients after they received NB-UVB for 4 th months, they are found higher than control and this agrees with Goldstein et al [22] who reported the effect of NB-UVB on proliferation and differentiation of Melscs.…”
Section: Discussionsupporting
confidence: 86%
“…Concomitant with these results, Yang et al 2016 [ 39 ] reported that initial activation of Notch1 signaling throughout wound healing could support EPSC proliferation and preserve their low differentiation potential and even multi-directional differentiation potential. Furthermore, Yang et al 2016 [ 39 ] and Zhou et al 2018 [ 40 ] stated that Notch1 is extensively expressed on EPSCs which were traced mainly in the basal layer of the epidermis, so, if the Notch signaling pathway was blocked, EPSC proliferation would be inhibited hindering the epithelialization process leading to loss of skin barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin is an important structural protein of epidermal cells. The different degrees of differentiation of epidermal cells can be used to express different characteristics of keratin, which can be used for identifying EpiSCs, TACs, and TDCs [31]. EpiSCs express mainly keratin 15 and 19 (CK15 and CK19); TACs express keratin 5 and 14 (CK5 and CK14); and TDCs express keratin 1 and 10 (CK1 and CK10).…”
Section: Keratinmentioning
confidence: 99%